Mutual Fund Flows and Benchmark Portfolio Returns - Kvamvold, Joakim (International Journal of Economics and Financial Issues, 2017)
We examine trading caused by net flows to mutual funds invested at the Oslo Stock Exchange. Our results show that trading by index-linked mutual funds and actively managed funds are correlated with returns on different segments of the stock exchange. Neither investor sentiment, nor feedback trading explain this correlation. We argue that information cannot explain the results. Hence, we provide evidence that changes in demand matters for stock prices. Keywords : Mutual funds, investment flows, portfolio returns. JEL classifications: G11, G12, G14